Barriers and facilitators of the reporting by family doctors of cases of domestic violence – a qualitative study across Portugal - Diana Nadine Moreira; Mariana Pinto da Costa (BMC Primary Care, 2024)
Abstract Background Domestic violence (DV) is a serious and prevalent public health problem with devastating consequences for the victims and their families. Whilst the number of cases reported to the authorities has risen in recent years, many victims still chose not to present a complaint. In Portugal, to address this, DV became a public crime. As victims of DV present multiple health problems and frequently seek professional help, family doctors are in a privileged position to detect and report cases of DV to the authorities. However, little is known about what motivates these professionals to report or not the DV cases they encounter in their practice to the authorities. Methods We conducted semi-structured interviews with family doctors from all regional health administrations of continental Portugal. Interviews occurred between July 2020 and September 2022, were conducted in person or remotely, audio recorded, transcribed, and analysed using thematic analysis. Content analysis was conducted to assess the agreement or disagreement regarding mandatory reporting in each of the themes and subthemes. Results Fifty-four family doctors took part in this study (n = 39 women, n = 15 men). The main themes that arose from the analysis were: “Barriers related to the physician’s activity,” “Barriers related to the victim or aggressor,” “Facilitators related to the physician’s activity,” “Facilitators related to the victim or aggressor.” Although different barriers were described, most doctors agreed with the mandatory reporting of DV cases. Conclusions Family doctors encounter multiple barriers and facilitators when considering reporting a DV case to the authorities. The results of this study can help develop new interventions to address the barriers described by the doctors, increasing their compliance with mandatory reporting, the protection of victims and the just persecution of the aggressor.